Management of Urinary Tract Infection in Pregnancy - L Rojas Pérez; B Cruz Basantes; L Rojas Cruz; A Rojas Cruz (ESPOCH Congresses, 2023)
Abstract Urinary tract infection is a frequent occurrence in pregnancy that can increase the risk of complications; therefore, it is essential to investigate it at the first prenatal consultation. It is classified as asymptomatic bacteriuria, cystitis, and pyelonephritis. This research aims to determine the most appropriate treatment for urinary tract infections during pregnancy according to the best available evidence. The methodology implemented a clinical question: What is the best treatment for urinary tract infections during pregnancy? The PICO format helped search for scientific information, such as the pregnant women's population with urinary tract infections, whether the intervention received was an antibiotic treatment, was the comparison a no antibiotic treatment, and the result of preventing complications during pregnancy. The databases consulted were PubMed, Cochrane Library, the ACCESSSS search engine, Epistemonikos, DynaMed, and UpToDate. As a result of the information search process, 305 articles were obtained, of which 255 were discarded for not being within the inclusion criteria and 51 were used in this investigation. Of these 50 articles, 15 were eliminated because they were duplicates and 37 were used in this review. In conclusion, urinary tract infection causes increased perinatal maternal morbidity and mortality; therefore, it is essential to investigate and treat it.